2019
DOI: 10.2147/ndt.s205612
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ginaton improves neurological function in ischemic stroke rats via inducing autophagy and maintaining mitochondrial homeostasis</p>

Abstract: Purpose The present study was carried out to confirm the protective effect of extract of Ginkgo biloba (Ginaton) against ischemic neuronal damage post-treatment at 24 h after reperfusion in rats with middle cerebral artery occlusion (MCAO) and further reveal its possible mechanisms. Methods Adult male Sprague-Dawley rats were modeled by MCAO for 2 h. The rats were divided into three groups: sham, model, and Ginaton (50 mg/kg). All animals rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Ao et al reported that JLX001 could induce autophagy to alleviate cerebral ischemia injury by activating the AMPK-ULK1 signaling pathway (Ao et al, 2019 ). The neuroprotective mechanisms of Ginaton in ischemic brain injury mainly include activation of AMPK pathway induced autophagy, maintenance of mitochondrial homeostasis, and inhibition of apoptosis (Li et al, 2019 ). On the other hand, He et al ( 2019 ) found that Puerarin inhibited neuronal autophagy and plays a neuroprotective role in cerebral ischemia (Hongyun et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ao et al reported that JLX001 could induce autophagy to alleviate cerebral ischemia injury by activating the AMPK-ULK1 signaling pathway (Ao et al, 2019 ). The neuroprotective mechanisms of Ginaton in ischemic brain injury mainly include activation of AMPK pathway induced autophagy, maintenance of mitochondrial homeostasis, and inhibition of apoptosis (Li et al, 2019 ). On the other hand, He et al ( 2019 ) found that Puerarin inhibited neuronal autophagy and plays a neuroprotective role in cerebral ischemia (Hongyun et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies including the present one examine the acute effects of BYHW on stroke, the effects of chronic treatment of BYHW are yet to be fully elucidated. Long-term effects of BYHW on suspected genes or target proteins related to inflammation and mitochondria homeostasis in ischemic stroke and peripheral artery diseases also warrant further research [9,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [63] observed an increased LC3-II protein level after cardiac arrest; that peaked between 3 and 6 h and then gradually decreased by 24 h. Wei et al [34] confirmed an early increase in LC3-II at 6 and 12 h within the cortex from mice subjected to cardiac arrest. However, Wu et al [64] and Li et al [65] observed lower levels of autophagy markers in the ischemic cortex compared to non-ischemic controls at days 7 and 14 post-ischemia. This is consistent with our observations of reduced hippocampal levels of LC3-II, indicating that autophagy was impaired at later time points after global ischemia when microglial activation peaks.…”
Section: Effects Of Stress Exposure Prior To Ischemia On Autophagymentioning
confidence: 93%